Impact of disease-causing mutations on inter-domain interactions in cMyBP-C: a steered molecular dynamics study. Issue 9 (4th July 2017) - Krishnamoorthy, Navaneethakrishnan; Gajendrarao, Poornima; Olivotto, Iacopo; Yacoub, Magdi
Abstract : The molecular interactions of the sarcomeric proteins are essential in the regulation of various cardiac functions. Mutations in the gene MYBPC3 coding for cardiac myosin-binding protein-C (cMyBP-C), a multi-domain protein, are the most common cause of hypertrophic cardiomyopathy (HCM). The N-terminal complex, C1-motif-C2 is a central region in cMyBP-C for the regulation of cardiac muscle contraction. However, the mechanism of binding/unbinding of this complex during health and disease is unknown. Here, we study possible mechanisms of unbinding using steered molecular dynamics simulations for the complex in the wild type, in single mutations (E258K in C1, E441K in C2), as well as in a double mutation (E258K in C1 + E441K in C2), which are associated with severe HCM. The observed molecular events and the calculation of force utilized for the unbinding suggest the following: (i) double mutation can encourage the formation of rigid complex that required large amount of force and long-time to unbind, (ii) C1 appears to start to unbind ahead of C2 regardless of the mutation, and (iii) unbinding of C2 requires larger amount of force than C1. This molecular insight suggests that key HCM-causing mutations might significantly modify the native affinity required for the assembly of the domains in cMyBP-C, which is essential for normal cardiac function.